Interaction of the craniofacial complex and velopharyngeal musculature on speech resonance in children with 22q11.2 deletion syndrome: An MRI analysis. Issue 1 (January 2021) - Kollara, Lakshmi; Baylis, Adriane L.; Kirschner, Richard E.; Bates, D. Gregory; Smith, Mark; Fang, Xiangming; Perry, Jamie L.
Summary: There are limited MRI studies of craniofacial and velopharyngeal features in children with 22q11.2 deletion syndrome (22q11.2DS) and to date, none have explored the potential relationship between these features and the speech phenotype. The purpose of this study was to examine the relationship between craniofacial and related velopharyngeal structures in children with 22q11.2DS and to assess their correlation to resonance features using an unsedated MRI protocol. Fifteen children with 22q11.2DS and 15 age- and sex-matched controls with normal velopharyngeal anatomy (ages 4–12 years) successfully completed the study. Analysis of covariance was used to compare differences between the experimental (22q11.2DS) and control (children with normal anatomy) groups. Correlation analyses and regression models were also utilized. The 22q11.2DS group demonstrated significantly shorter nasion-to-sella, sella-to-basion, and basion-to-opisthion distances. The anterior cranial base angle was significantly more obtuse. The levator veli palatini (levator) muscle was significantly thinner and shorter, with an obtuse angle of origin in the 22q11.2DS group. Levator length was significantly correlated with the sella-to-basion measure and hypernasality was correlated with levator origin-to-origin distance. Preliminary results from this study indicate a significant association between hypernasality and levator origin-to-origin distance. Findings from the present study, provide an insight into the pathophysiology of velopharyngeal dysfunction related to this clinically complex population.